Ferritin nanoconjugates guide trastuzumab brain delivery to promote an antitumor response in murine HER2 + breast cancer brain metastasis - Marta Sevieri; Serena Mazzucchelli; Linda Barbieri; Stefania Garbujo; Stephana Carelli; Arianna Bonizzi; Federica Rey; Camilla Recordati; Matteo Recchia; Raffaele Allevi; Leopoldo Sitia; Carlo Morasso; et al. (Elsevier, 2023)
Brain metastasis (BM) represents a clinical challenge for patients with advanced HER2 + breast cancer (BC). The monoclonal anti-HER2 antibody trastuzumab (TZ) improves survival of BC patients, but it has low central nervous system penetrance, being ineffective in treating BM. Previous studies showed that ferritin nanoparticles (HFn) may cross the blood brain barrier (BBB) through binding to the transferrin receptor 1 (TfR1). However, whether this has efficacy in promoting the trans-BBB delivery of TZ and combating BC BM was not studied yet. Here, we investigated the potential of HFn to drive TZ brain delivery and promote a targeted antitumor response in a murine model of BC BM established by stereotaxic injection of engineered BC cells overexpressing human HER2. HFn were covalently conjugated with TZ to obtain a nanoconjugate endowed with HER2 and TfR1 targeting specificity (H-TZ). H-TZ efficiently achieved TZ brain delivery upon intraperitoneal injection and triggered stable targeting of cancer cells. Treatment with H-TZ plus docetaxel significantly reduced tumor growth and shaped a protective brain microenvironment by engaging macrophage activation toward cancer cells. H-TZ-based treatment also avoided TZ-associated cardiotoxicity by preventing drug accumulation in the heart and did not induce any other major side effects when combined with docetaxel. These results provided in vivo demonstration of the pharmacological potential of H-TZ, able to tackle BC BM in combination with docetaxel. Indeed, upon systemic administration, the nanoconjugate guides TZ brain accumulation, reduces BM growth and limits side effects in off-target organs, thus showing promise for the management of HER2 + BC metastatic to the brain.